Representations of Insanity in Selecter Works of Edgar Allan Poe - Pachulski, Filip (Univerzita Pardubice, 2018)
This bachelor paper is generally concerned with the mental states of the characters in selected tales by Edgar Allan Poe, specifically The Tell-Tale Heart and The Black Cat. The aim of this thesis is to analyze the two stories from a narratological point of view and determine whether or not their narrators can be considered reliable and whether are not they can be considered insane.
Zpodobnění šílenství ve vybraných dílech Edgara Allana Poea
Keywords: Poe, Edgar Allan; šílenství; naratologie; Černý kocour; Zrádné srdce; psychické zdraví; Poe, Edgar Allan; insanity; narratology; Black Cat; Tell-Tale Heart; mental health